ANTECEDENTS AND CONSEQUENCES OF FEAR OF CHILDBIRTH IN NULLIPAROUS AND PAROUS WOMEN. Issue 1 (1st December 2014) - Pazzagli, Chiara; Laghezza, Loredana; Capurso, Michele; Sommella, Ciro; Lelli, Franco; Mazzeschi, Claudia
ABSTRACT The study aimed to explore the differences in the role of specific personal and interpersonal risk factors in predicting fear of childbirth (FOC) and to examine whether FOC predicts postnatal maternal adaptation in nulliparous and parous women. A prospective correlational design with two time periods (pre‐ and postnatal) was carried out with 158 women, 85 nulliparous and 73 parous. Women at Week 32 of gestation completed a demographic questionnaire, the Wijma Delivery Expectancy Questionnaire (K.Wijma, B. Wijma, & M. Zar, 1998), the State‐Trait Anxiety Inventory (C.D. Spielberger, R.L. Gorsuch, & R.E. Lushene, 1970), the Symptom Checklist‐90‐Revised (L.R. Derogatis, 1983), the Dyadic Adjustment Scale (G.B. Spanier, 1976), and the Reciprocal Attachment Questionnaire (M. West, A. Sheldon, & L. Reiffer, 1987). Three months after delivery, the women completed the Edinburgh Postnatal Depression Scale (J.L. Cox, J.M. Holden, & R. Sagovsky, 1987) and the Parenting Stress Index‐Short Form (R. Abidin, 1986). Pearson's correlations and a series of multiple regressions were conducted. The results indicated that in the prenatal period, higher state anxiety, β = .35, p < .001, lower dyadic adjustment, β = −.26, p = .03, and higher insecurity in attachment relationships, β = .39, p < .001, predicted FOC in first‐time mothers only. In the postnatal period, FOC predicted postnatal maternal risk for depression, β = .39, p = .02, and parenting stress, β = .42, p = .02, for nulliparous women only. The specific antecedents and consequences of FOC in nulliparous and parous women should be taken into consideration when developing specific interventions.